2024
DOI: 10.1007/s00383-023-05619-3
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing enterocolitis: current understanding of the prevention and management

Xiaohan Hu,
Hansi Liang,
Fang Li
et al.

Abstract: Necrotizing enterocolitis (NEC) is one of the diseases in neonates, with a high morbidity and mortality rate, especially in preterm infants. This review aimed to briefly introduce the latest epidemiology, susceptibility factors, and clinical diagnosis and presentation of NEC. We also organized new prevention strategies by risk factors according to different pathogeneses and then discussed new treatment methods based on Bell's staging and complications, and the classification of mild to high severity based on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 179 publications
1
1
0
Order By: Relevance
“…The incidence of NEC in this study was within the current prevalence at 6.9% [54]. As with other studies [55], we found racial disparities amongst our NEC cases, with BPT infants having a higher incidence of NEC at 7.5% versus WPT infants at 6.5% (p = 0.7545).…”
Section: Discussionsupporting
confidence: 86%
“…The incidence of NEC in this study was within the current prevalence at 6.9% [54]. As with other studies [55], we found racial disparities amongst our NEC cases, with BPT infants having a higher incidence of NEC at 7.5% versus WPT infants at 6.5% (p = 0.7545).…”
Section: Discussionsupporting
confidence: 86%
“…Necrotizing enterocolitis (NEC) is a complex inflammatory gastrointestinal disease with devastating sequelae (1). Despite decades of research to identify predisposing factors and effective treatments, NEC remains a leading cause of morbidity and mortality in neonatal intensive care units, especially in low birth weight infants (2). Related mortality rates remain unacceptably high, surpassing 50% in affected infants requiring surgery for NEC (3).…”
Section: Introductionmentioning
confidence: 99%